2017
DOI: 10.1039/c7tx00144d
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of pesticide aquatic toxicity with chemical category approaches

Abstract: Aquatic toxicity is an important issue in pesticide development. In this study, using nine molecular fingerprints to describe pesticides, binary and ternary classification models were constructed to predict aquatic toxicity of pesticides six machine learning methods: Naïve Bayes (NB), Artificial Neural Network (ANN), k-Nearest Neighbor (kNN), Classification Tree (CT), Random Forest (RF) and Support Vector Machine (SVM). For the binary models, local models were obtained with 829 pesticides on rainbow trout (RT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 56 publications
3
26
0
Order By: Relevance
“…The best performances are obtained by the RF, followed by the DF-RASAR and other models that obtained performances that were not too far. This similarity between different models was already found previously [11,13], and the superiority of RFs had already been pointed out [13]. Even though the DF-RASAR obtains good performances, they do not seem to outperform other traditional machine learning models.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The best performances are obtained by the RF, followed by the DF-RASAR and other models that obtained performances that were not too far. This similarity between different models was already found previously [11,13], and the superiority of RFs had already been pointed out [13]. Even though the DF-RASAR obtains good performances, they do not seem to outperform other traditional machine learning models.…”
Section: Discussionsupporting
confidence: 79%
“…Estimates of y2 from the whole dataset x = ( x ch , xtax, xex), using the distances defined in Eq. (11). We only list the models that rely on the definition of the distance [Eqs.…”
Section: The Ct E Setup: Combining Chemical Taxon and Experimental De...mentioning
confidence: 99%
See 1 more Smart Citation
“…Where the resulted peptides were found to be non-toxic and there were mutations found on the sequences. It showed good scores that ranged from -0.37 to -1.38 which is consistent with global binary models (Li et al,2017). The molecular weights were was within 500KD which is an ideal mass for a drug.…”
Section: In Silico and Molecular Docking Studies Toxicity Prediction ...supporting
confidence: 72%
“…Our group previously collected LC 50 data of three fish species from ECOTOX database and built several local and global models (Sun et al, 2015 ). Recently, we reported a model focusing on the aquatic toxicity of pesticides and found that the molecule fingerprints performed different between local and global models (Li et al, 2017 ). For the avian species, several in silico models were developed including classification (Zhang et al, 2015 ) and regression (Mazzatorta et al, 2006 ; Toropov and Benfenati, 2006 ).…”
Section: Progress In Toxicity Predictionmentioning
confidence: 99%